(untitled) (Journal of Plant Disease Sciences, 2021)
Published research on post-harvest efficacy and proper management of chlorination for specific fruits and vegetables has been largely focused on tomato, potato, apple, and pear. As there were some reports of chlorination for reducing post-harvest losses of citrus an experiment was formulated to standardize the doses and exposure time of Sodium Hypochloride (NaOCl) sanitization to restrict Penicillium rot of Nagpur Mandarins, a major storage disease in India. In this experiment Nagpur mandarin fruits pre-inoculated with P. digitatum were exposed to NaOCl solution at 3 concentrations and 4 exposure times followed by application of 6% Vegetable/Citracine wax and the observation for disease development were recorded for 5-time intervals upto 15th day of storage under ambient condition. This study revealed that among all the treatments 10 min exposure at 1.0% concentration of NaOCl followed by application of 6% Vegetable/ Citracine wax gave best results in controlling blue mould disease.